2019
DOI: 10.1007/s00535-019-01652-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term proton pump inhibitor usage and the association with pancreatic cancer in Sweden

Abstract: Background The long-term safety of proton pump inhibitors (PPIs) is increasingly questioned. The aim of our study was to assess the risk of pancreatic cancer among longterm PPI users in Sweden. Methods This population-based nationwide Swedish cohort study including 796,492 adult long-term PPI users has been used to calculate the standardized incidence rate ratios (SIRs) and 95% confidence intervals (CI) for pancreatic cancer, stratifying by indications of use, age, sex, and duration of use. The risk among all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 51 publications
1
37
0
3
Order By: Relevance
“…They were published between 2012 and 2020 in six countries. Three studies were conducted in the UK [ 36 , 37 , 41 ], two in the USA [ 32 , 42 ], two in Taiwan [ 30 , 33 ], one in Korea [ 35 ], one in Denmark [ 34 ] and one in Sweden [ 43 ]. The follow-up duration was between 5 and 20 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were published between 2012 and 2020 in six countries. Three studies were conducted in the UK [ 36 , 37 , 41 ], two in the USA [ 32 , 42 ], two in Taiwan [ 30 , 33 ], one in Korea [ 35 ], one in Denmark [ 34 ] and one in Sweden [ 43 ]. The follow-up duration was between 5 and 20 years.…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis of pancreatic cancer was based on the ICD codes in six studies [ 30 , 32 , 33 , 35 , 42 , 43 ], medical record code in two studies [ 36 , 37 ], and histological verification of PDA in two studies [ 34 , 41 ]. Stratified analysis according to the PPI dose and duration was performed in five studies [ 32 , 33 , 34 , 35 , 36 ] and in the five other studies [ 32 , 33 , 36 , 37 , 43 ], respectively, although they all used a different cutoff value of dose and duration. In six studies, pancreatic cancer cases that developed within 1 or 2 years after PPI introduction were excluded because PPI was probably used to help in treating and diagnosing cancer-associated symptoms [ 30 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that the common bile duct stent may affect the duodenal microbiome. Many clinical factors such as proton pump inhibitors may affect the composition of colonized microbiome in the pancreas and increase the risk of pancreatic cancer ( 43 , 44 ).…”
Section: Composition Of Microorganisms Colonized In Pancreatic Cancermentioning
confidence: 99%
“…Selv om observasjonsstudier har vist til dels motstridende resultater, har nyere registerstudier og metaanalyser vist at langvarig bruk av protonpumpehemmere dobler risikoen for kreft i pankreas og magesekk. Enkelte studier har vist økt risiko for kolorektalkreft (4)(5)(6).…”
Section: Alvorlige Langtidskonsekvenserunclassified